e-Health/m-Health Adoption and Lifestyle Improvements: Exploring the Roles of Technology Readiness, the Expectation-Confirmation Model, and Health-Related Information Activities - Louis Leung; Chris Cheng Chen (International Telecommunications Society (ITS), 2017)
This purpose of this study was to investigate (a) the prevalence and patterns of e-health/m-health usein Hong Kong;(b) the activities that people engage in via health-related information platforms/apps;and (c) the roles thattechnology readiness, the expectation-confirmation model, and e-health/m-health activities play in predicting lifestyle improvement. Data were collected from a telephone survey, with a probability sample of 1,007 respondents aged 18 or above. Our results show that 47.2% of the respondents were regular users of e-health technologies, 23.2% were m-health users, and only 10.7% used wearables for health purposes. Among the six e-health/m-health activities identified, health tutorials and health information seeking were the most frequently used, followed by recording/monitoring and medical services. The least popular activities were reminders and sharing experiences. As expected, the component variables in the expectation-confirmation model, particularly confirmation and perceived usefulness, were the strongest predictors for lifestyle improvement. External factors, such as being older and innovative, the use of e-health/m-health activities for recording/monitoring, health tutorials, medical services, and sharing experiences, also had significant impacts. Theoretical and practical implications are discussed.
Keywords: 330; e-health/m-health; expectation-confirmation model; technology readiness; health-related activities; lifestyle improvements